Risk of work-related hand eczema in relation to wet work exposure - Tamara Lund; Sesilje Bondo Petersen; Esben Meulengracht Flachs; Niels Erik Ebbehøj; Jens Peter Bonde; Tove Agner (Nordic Association of Occupational Safety and Health (NOROSH), 2020)
OBJECTIVE: Albeit a pivotal risk for the development of hand eczema (HE), the exposure-response relationship between wet work and HE remains to be further investigated. Knowledge on exposure-response is important regarding preventive measures, medico-legal regulations and job-counseling. Recently, a job-exposure matrix (JEM) for wet work was developed, providing information on the likelihood of wet work. By combining the JEM with data on HE we aimed to investigate the relationship between extent of wet work and HE. METHODS: This study is a case-referent study including patients registered in the National Database of Contact Allergy, Denmark, and comprises data on sex, age, atopic dermatitis, HE, face eczema and patch testing results. Patients with HE served as cases and patients with facial eczema served as referents. Information on profession was retrieved from the DOC*X database in accordance with the DISCO-88 classification system. A wet-work-specific JEM provides - for each profession - an estimate for (i) the likelihood of wet work lasting ≥2 hours/day and (ii) the average number of hours of wet work per day. RESULTS: After two hours of wet hands and glove wear, the odds ratio (OR) was 3.49 and 3.19, respectively, for females and 2.41 and 1.82, respectively, for males. Females had a higher risk of HE than males with probability of wet hands <75% (OR 2.34, 95% CI 2.12-2.58 compared to males 1.68, 95% CI 1.22-2.31) and regarding glove wear at all exposure levels. CONCLUSION: Our data confirms a close association between wet work and HE. Exposure lasting less than the current definition of wet work (having wet hands for ≥2 hours per day) may be of importance.